Estimating Braking Performance in Osteoarthritis of the Knee or Hip with a Reaction Timer. Issue 2 (3rd April 2019) - von Bernstorff, Maximilian; Rapp, Jennifer; Bausenhart, Felix; Feierabend, Martina; Ipach, Ingmar; Hofmann, Ulf K
Abstract : Objective: To investigate if testing in a brake simulator can be replaced by a simple reaction timer setup imitating the ergonomic conditions of emergency braking when evaluating the ability to drive in patients with musculoskeletal problems of the lower extremities. Methods: A cross‐sectional survey was performed in the Department of Orthopaedic Surgery in our University Hospital from October 2014 until May 2015. Patients attending our department with either osteoarthritis or arthroplasty of the knee or hip were asked to participate in the study if they had a valid driving license. The age limit was from 18 to 85 years. Both women and men were included. Registered demographic data were patient age, height, sex, body weight, and body mass index. Braking performance (brake response time [BRT]) was evaluated in a brake simulator that was embedded into a real car cabin (10 measurements). The values obtained were compared with those registered when simply testing (5 measurements) those patients with a normal reaction timer setup that imitated the sitting position in a car. Kendall's tau correlation coefficient was calculated between the values obtained from the brake simulator with those from the reaction timer setup. Results: Altogether, 137 patients (median age 67 years [range, 24–89 years]) with either osteoarthritis of the knee (n = 55) or hip (n = 82) were tested. Age was comparable in both collectives ( P = 0.807). The mean body height was 1.70 m in both groups. Knee patients presented with a higher body weight of approximately 5 kg ( P = 0.014) and consequently also had a higher body mass index ( P = 0.023). The median BRT in the brake simulator was 628 ms (range, 390–1444 ms) for all subjects: 592 ms (range, 418–1146 ms) in the hip group and 696 ms (range, 390–1444 ms) in the knee group. Measurement values obtained by the reaction timer were significantly ( P < 0.001) higher by approximately 15% (SD, 22%) than those measured in the brake simulator. A moderate correlation was found between the reaction timer and the brake simulator, with a Kendall's tau of 0.449 ( P < 0.001) for all patients. Interestingly, hip patients showed a higher correlation ( τ = 0.471) than knee patients ( τ = 0.263). Conclusion: Even though the measured correlations do not allow us to make a definite statement concerning braking performance, especially in knee patients, a simple reaction timer test can provide a low‐cost first estimate of BRT for patients and their treating physicians. For forensic statements, the brake simulator will, however, remain the gold standard.